2014
DOI: 10.1177/1087054714542003
|View full text |Cite
|
Sign up to set email alerts
|

Self- and Parent-Rated Quality of Life of a Treatment Naïve Sample of Children With ADHD: The Impact of Age, Gender, Type of ADHD, and Comorbid Psychiatric Conditions According to Both a Categorical and a Dimensional Approach

Abstract: Our results draw the attention to the importance of taking into account age, gender, and both self- and parent reports when measuring QoL of children with ADHD and both dimensional and categorical approaches should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
(35 reference statements)
1
23
0
4
Order By: Relevance
“…Although several researcher highlight that next to children's self-reported QoL, parents' views about their children's QoL should be measured, there is discrepancy between the agreement of parent-child proxy reports on children's QoL in the majority of the studies (Bastiaansen et al, 2004; Britto et al, 2004; Chang and Yeh, 2005; Cremeens et al, 2006; Russell et al, 2006; Eiser and Jenney, 2007; Jozefiak et al, 2008; Upton et al, 2008; Danckaerts et al, 2009; Eiser and Varni, 2013; Dallos et al, 2014), including the very few ones on children with SpLD (Rotsika et al, 2011; Karande and Venkataraman, 2013). Comparing the QoL of children with SpLD and typically developed peers (Rotsika et al, 2011), found significant differences between the parent-child proxy ratings: mothers of children with SpLD reported significantly lower scores regarding the child's functioning in school, but significantly higher scores in their physical and emotional well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several researcher highlight that next to children's self-reported QoL, parents' views about their children's QoL should be measured, there is discrepancy between the agreement of parent-child proxy reports on children's QoL in the majority of the studies (Bastiaansen et al, 2004; Britto et al, 2004; Chang and Yeh, 2005; Cremeens et al, 2006; Russell et al, 2006; Eiser and Jenney, 2007; Jozefiak et al, 2008; Upton et al, 2008; Danckaerts et al, 2009; Eiser and Varni, 2013; Dallos et al, 2014), including the very few ones on children with SpLD (Rotsika et al, 2011; Karande and Venkataraman, 2013). Comparing the QoL of children with SpLD and typically developed peers (Rotsika et al, 2011), found significant differences between the parent-child proxy ratings: mothers of children with SpLD reported significantly lower scores regarding the child's functioning in school, but significantly higher scores in their physical and emotional well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Although the construct of the quality of life (QoL)—which includes psychical, psychological, and social aspects—has been recently gaining importance as a multidimensional measure of overall well-being of children with psychiatric problems (Bastiaansen et al, 2004, 2005; Dallos et al, 2014), there is very little research on the QoL in children with RD (Karande et al, 2009; Rotsika et al, 2011; Karande and Venkataraman, 2012, 2013; Ginieri-Coccossis et al, 2013). All these studies examined children with SpLD and not only children with RD.…”
Section: Introductionmentioning
confidence: 99%
“…As an important measure of individuals’ general state, the concept of quality of life (QoL) and its relationship with physical and mental health disorders has received increased attention over recent years [28,29]. Research shows, that subjective well-being is an important dimension of overall perceived QoL [30].…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios también han determinado que existen variables sociodemográficas, clínicas, neuropsicológicas y académicas que son determinantes para la percepción de CV en niños con TDAH (18,19).…”
Section: Introductionunclassified